Self-assembled quasi-hexagonal arrays of gold nanoparticles with small gaps for surface-enhanced Raman spectroscopy - Gürdal, Emre; Dickreuter, Simon; Noureddine, Fatima; Bieschke, Pascal; Kern, Dieter P.; Fleischer, Monika (Beilstein Journal of Nanotechnology, 2018)
The fabrication and optical characterization of self-assembled arrangements of rough gold nanoparticles with a high area coverage and narrow gaps for surface-enhanced Raman spectroscopy (SERS) are reported. A combination of micellar nanolithography and electroless deposition (ED) enables the tuning of the spacing and size of the noble metal nanoparticles. Long-range ordered quasi-hexagonal arrays of gold nanoparticles on silicon substrates with a variation of the particle sizes from about 20 nm to 120 nm are demonstrated. By increasing the particle sizes for the homogeneously spaced particles, a large number of narrow gaps is created, which together with the rough surface of the particles induces a high density of intense hotspots. This makes the surfaces interesting for future applications in near-field-enhanced bio-analytics of molecules. SERS was demonstrated by measuring Raman spectra of 4-MBA on the gold nanoparticles. It was verified that a smaller inter-particle distance leads to an increased SERS signal.
Keywords: block copolymer; electroless deposition; gold nanoparticles; micelle lithography; optical antenna; self-assembly; SERS